Prevalence of Extended Spectrum Beta Lactamase (ESBL) Producing Gram Negative Isolates in Neonates - N. Shah, Manisha (Innovations in Microbiology and Biotechnology Vol. 2, 2021)
Objectives: Emergence of clinical isolates with extended spectrum beta lactamase (ESBL) producing capabilities has created therapeutic challenges. Thus, ESBLs are of increasing clinical concern in worldwide as confers resistance to broad spectrum \(β\)-lactam antibiotics. Because neonates are more prone to infections, it is a major concern chiefly in Neonatal Intensive Care Units (NICUs). It is responsible for therapeutic failure and neonatal mortality when neonates are treated with cephalosporins; hence its detection and knowledge of present scenario of prevalence is crucial for infection control. The present study explored the incidences of ESBL producers among infectious neonates included under the study. Materials and Methods: 1611 suspected cases of neonatal infections were included under study during 25 months (December 2010 to January 2013). Among 342 positive cases, 211 were identified as gram negative by strict microbiological standards and were checked for ESBLs productions. Double disc diffusion test was used for suspection of ESBL production and were further confirmed by the double disc synergy test (DDST) and the phenotypic confirmatory disc diffusion test (PCDDT). Results: Out of the 212 isolates, 39.34% screened as prospective ESBLs producers. 29.39% were confirmed by DDST and 27.97% by PCDDT. Escherichia coli were the most common ESBL producers found followed by K. pneumoniae. Finally, high prevalence of ESBL producers in N.I.C.Us., knocking the essentiality of detection of ESBL production routinely with sensitivity reports that may guide neonatologist to accomplish the therapeutic challenge